Sequential therapy involving an early switch from entecavir to pegylated interferon‐α in Japanese patients with chronic hepatitis B. Issue 6 (12th February 2018) - Enomoto, Masaru; Nishiguchi, Shuhei; Tamori, Akihiro; Kozuka, Ritsuzo; Fujii, Hideki; Uchida‐Kobayashi, Sawako; Fukunishi, Shinya; Tsuda, Yasuhiro; Higuchi, Kazuhide; Saito, Masaki; Enomoto, Hirayuki; Kawada, Norifumi
Abstract : Aim: The optimal combination of two currently available agents with different mechanisms of action, a nucleos(t)ide analog and pegylated interferon‐α (PegIFNα), must be determined to improve treatment of chronic hepatitis B (CHB). Methods: In this study, 24 patients with CHB (14 hepatitis B envelope antigen [HBeAg]‐positive patients and 10 HBeAg‐negative patients) received entecavir for 36–52 weeks, followed by entecavir plus Peg‐IFNα2a for 4 weeks, and finally by PegIFNα‐2a alone for 44 weeks. Results: A sustained biochemical, virologic, and serologic response was obtained in 7/24 (29%) patients at 48 weeks post‐treatment (2/14 [14%] in HBeAg‐positive vs 5/10 [50%] in HBeAg‐negative patients, P = 0.085). At baseline, patients with a sustained response had a significantly lower γ‐ glutamyl transferase level ( P = 0.0023), a lower aspartate aminotransferase‐to‐platelet ratio index ( P = 0.049), and a lower α‐fetoprotein level ( P = 0.042) than those without a sustained response. The decline in hepatitis B surface antigen (HBsAg) levels during the first 24 weeks of PegIFNα‐2a treatment in patients with a sustained response was greater than that in patients without ( P = 0.017). Additionally, HBsAg seroclearance was achieved in two patients (8.3%): one HBeAg‐positive and one HBeAg‐negative patient. Conclusion: The outcomes of sequential therapy involving an early switch from entecavir to PegIFNα‐2a were unsatisfactory in Japanese patients with CHB. In addition to viral factors, host metabolic characteristics and liver fibrosis/tumor markers can be used for prediction of a sustained response to therapy, but accurate prediction of the therapeutic response is difficult.